Introduced and native herbivores have different effects on plant composition in low productivity ecosystems. Issue 1 (10th October 2017) - Travers, Samantha K.; Eldridge, David J.; Dorrough, Josh; Val, James; Oliver, Ian
Abstract: Questions: Understanding how livestock grazing alters plant composition in low productivity environments is critical to managing livestock sustainably alongside native and introduced wild herbivore populations. We asked four questions: (1) does recent livestock and rabbit grazing reduce some plant attributes more strongly than others; (2) does grazing by introduced herbivores (i.e. livestock and rabbits) affect plants more strongly than native herbivores (i.e. kangaroos); (3) do the effects of recent livestock grazing differ from the legacy effects of livestock grazing; and (4) does the probability of occurrence of exotic plants increase with increasing net primary productivity (NPP)? Location: South‐eastern Australia. Methods: We measured the recent grazing activity of co‐occurring livestock (cattle, sheep, goats), rabbits and kangaroos by counting faecal pellets; historic grazing activity by measuring livestock tracks; and derived NPP from satellite imagery. We used a hierarchical GLMM to simultaneously model the presence or absence (i.e. probability of occurrence) of all plant species as a function of their attributes (growth form, lifespan and origin) to assess their average response to recent grazing, historic grazing and productivity in a broad‐scale regional study. Results: Recent and historic livestock grazing, rabbit grazing and increasing NPP reduced the average probability of occurrence of plant species, although responses varied among plant attributes. Both recent and historic livestock grazing strongly reduced the average probability of occurrence of native species, and forbs and geophytes, but differed in their relative effects on other growth forms. Recent livestock grazing, rabbit grazing and NPP had similar effects, strongly reducing native species and forbs, geophytes, shrubs and sub‐shrubs. The overall effects of recent kangaroo grazing were relatively weak, with no clear trends for any given plant attribute. Conclusion: Our results highlight the complex nature of grazing by introduced herbivores compared with native herbivores on different plant attributes. Land managers need to be aware that domestic European livestock, rabbits and other free‐ranging introduced livestock such as goats have detrimental impacts on native plant communities. Our results also show that kangaroo grazing has a relatively benign effect on plant occurrence. Abstract : It is important to manage livestock sustainably alongside wild herbivores. We assessed the effects of productivity and grazing activity of livestock (cattle, sheep, goats), rabbits and kangaroos on the occurrence of plants as a function of their attributes (growth form, lifespan, origin). We found livestock and rabbits have detrimental impacts on native plant communities, but kangaroo grazing is relatively benign.